Solar reflectance of ETICS finishing coatings - a comparison of experimental techniques - Nuno M. M. Ramos (2020)
The solar reflectance has a significant role in the thermal behaviour and surface temperature of ETICS finishing coats. Incomplete information of solar reflectance of ETICS with nanopigments can sometimes difficult their adequate selection. In this work, the solar reflectance of different ETICS finishing coats was measured using two distinct methodologies, and the importance of the adopted procedure was discussed. The experimental methodologies used were: i) the adapted conventional pyranometer technique (non-ASTM E 1918A), which measures the global solar reflectance; and ii) the use of the spectrophotometry, to measure the spectral reflectance. It was verified that the El 918A methodology is more sensitive to environmental conditions than the spectrophotometry procedure. Also, the calculation of solar reflectance with spectrophotometer can be carried out by the 50 or 100 ordinates. However, the surface characteristics, as the concentration of pigments and roughness, affect more the solar reflectance measured with the spectrophotometer than with the pyranometer. It was verified that the nanopigments could improve solar reflectance and change the spectral reflectance. The results showed that, if the procedure is well applied, both methodologies could be used to evaluate the advantages of incorporating nanopigments in facade finishing coatings and also to assess the durability of these materials.